2019
DOI: 10.1108/ihr-09-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

A recommended closed-loop assessment of learning outcomes process for hospitality programs

Abstract: Purpose Because of the increasingly higher expectations of accrediting organizations, calls for greater accountability from state governments, and students’ demand for an education that prepares them for a career, most hospitality programs are now required to have an effective assessment of learning outcomes process. The increasing popularity of the assessment of learning outcomes process is viewed as highly positive because it can be considered as best practices in higher education. The paper aims to discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Primarily, this refers to constructive alignment. This is supported by Reich et al (2019a) and Gunarathne et al (2019) and further asserts that this is part of the continuous quality improvement that can help academics understand and uncover the methods of teaching and assessing students in a dynamic environment. It is also suggested that the OBE and constructive alignment processes should include relevant stakeholders such as industry experts and alumni for insights and suggestions on the programmes.…”
Section: Literature Reviewmentioning
confidence: 85%
See 4 more Smart Citations
“…Primarily, this refers to constructive alignment. This is supported by Reich et al (2019a) and Gunarathne et al (2019) and further asserts that this is part of the continuous quality improvement that can help academics understand and uncover the methods of teaching and assessing students in a dynamic environment. It is also suggested that the OBE and constructive alignment processes should include relevant stakeholders such as industry experts and alumni for insights and suggestions on the programmes.…”
Section: Literature Reviewmentioning
confidence: 85%
“…Observations and questioning were conducted on the academics and administrative staff to identify outcomes and challenges of the OBE process. This was important as it allowed insight and suggestions to be collected from academics and administrative staff that would ensure the successful implementation of the OBE process (Barradell, 2012;Hill & Wang, 2018;Reich et al, 2019a).…”
Section: Methodologiesmentioning
confidence: 99%
See 3 more Smart Citations